The Construction of Biomimetic Cementum Through a Combination of Bioskiving and Fluorine-Containing Biomineralization - Yang, Tao; Li, Yanshan; Hong, Yubing; Chi, Li; Liu, Chuanzi; Lan, Yu; Wang, Qinmei; Yu, Yingjie; Xu, Qiaobing; Teng, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Despite tremendous attention is given to the construction of biomimetic cementum for regeneration of tooth cementum, the lack of recapitulating the composition and hierarchical structure of cementum often leads to the poor performance of constructed materials. How to highly mimic the sophisticated composition and hierarchy of cementum remains a longstanding challenge in constructing the biomimetic cementum. Inspired by cementum formation process, a novel construction approach via a combination of bioskiving and fluorine-containing biomineralization is developed in this study. The alternative collagen lamellae that can highly mimic the rotated plywood structure of cementum collagen matrix is fabricated via bioskiving. Followed by biomineralization in the amorphous calcium phosphate solution with different concentration of fluorine, a series of biomimetic cementum is constructed. Screened by physicochemical characterization, the biomimetic cementum with the composition and hierarchical structure highly similar to human cementum is selected. Through in vitro biological assay, this biomimetic cementum is proven to significantly promote the adhesion, proliferation and cementogenic differentiation of periodontal ligament cells. Furthermore, in vivo study demonstrates that biomimetic cementum could induce cementogenesis. This biomimetic cementum constructed via combinatory application of bioskiving and fluorine-containing biomineralization stands as a promising candidate for achieving cementum regeneration.